Outpatient treatment engagement after suicidal attempt: A multisite prospective study. (December 2017) - Costemale-Lacoste, Jean-François; Balaguer, Elsa; Boniface, Bruno; Ivascu, Emil-Bogdan; Bernardini, Caroline; Metton, Jean-Pierre; Bouhlal, Ahmed; Ghanem, Teim; Corruble, Emmanuelle; Hardy, Patrick; Hozer, Franz; ,
Abstract: After suicidal attempt, the rate of specialized out treatment engagement (SOTE) does not exceed 30–50%. We designed a multisite prospective naturalistic study, in order to investigate predictive factors of SOTE after emergency department discharge among 107 suicidal attempters without current psychiatric ambulatory care. Both bivariate and multivariate analyses highlighted that booking an appointment with a mental health professional before discharge was significantly associated with higher SOTE rate. Psychiatric caregivers of emergency departments should be informed that this approach is a simple, fast way to improve SOTE among this population. Highlights: Ambulatory care among suicidal attempters is one of the main treatment intervention for preventing repetition and suicide. We conducted a prospective naturalistic study to identify predictive factors of specialized out treatment engagement (SOTE). Booking an appointment with a mental health professional is associated with higher rate of SOTE after 1 and 3 months. Such approach is a no time consuming simple way to improve SOTE in the short to medium term.